Recurrent pregnancy loss: can factor V Leiden mutations be a cause - R R N Reddy; Deepti Mutreja; Nikhil Moorchung; Indrayani Mukhopadhyay (Korean Society of Obstetrics and Gynecology, 2019)
The role of Factor V Leiden (FVL) mutation in recurrent miscarriages has been disputed. It has been hypothesized that FVL mutation in patients with recurrent miscarriages is treatable. In this study, we evaluated 78 pregnant women for FVL mutations, among whom 50 had a history of recurrent miscarriages. Only 1 (2%) of the woman was positive for heterozygous FVL mutation. The incidence of FVL mutations in patients with recurrent pregnancy loss had an odds ratio of 1.72 (95% confidence interval, 0.0681-43.8257; P>0.05). However, the findings were not statistically significant. Thus, we suggest that FVL mutation study may not be included in the battery of tests for recurrent miscarriages in the Indian population.